Advances on Smart Cities and Smart Buildings - Roccotelli, Michele; Mangini, Agostino Marcello (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Modern cities are facing the challenge of combining competitiveness at the global city scale and sustainable urban development to become smart cities. A smart city is a high-tech, intensive and advanced city that connects people, information, and city elements using new technologies in order to create a sustainable, greener city; competitive and innovative commerce; and an increased quality of life. This Special Issue collects the recent advancements in smart cities and covers different topics and aspects.